Functional study of the Nha1p C-terminus: involvement in cell response to changes in external osmolarity - Kinclova-Zimmermannova, Olga; Sychrova, Hana (Current genetics, 2006)
Saccharomyces cerevisiae uses different mechanisms to adapt to changes in environmental osmolarity. Upon hyperosmotic shock, cells first mobilize a rapid rescue system that prevents excessive loss of ions and water; then in the adaptation period they accumulate a compatible solute (glycerol). When subjected to hypoosmotic shock, they rapidly release intracellular stocks of glycerol to reduce intracellular osmolarity and prevent bursting. The plasma membrane Nha1 alkali metal cation/H+ antiporter is not important in helping the cells to survive a sudden drop in external osmolarity, but is involved in the cell response to hyperosmotic shock. For this role, its long hydrophilic C-terminus is indispensable. The capacity of the Nha1 antiporter to transport potassium is regulated by Hog1 kinase. Upon sorbitol-mediated stress, the Nha1p potassium export activity decreases in order to maintain a higher intracellular concentration of solutes. The C-terminal-less Nha1 version is not inactivated and its potassium efflux activity renders cells very sensitive to hyperosmotic shock. Taken together, our results suggest an important role of Nha1p and its C-terminus in the immediate response to hyperosmotic shock as part of the rapid rescue mechanism.
Keywords: upregulace; Membrane Proteins; proteiny přenášející kationty; Cation Transport Proteins; Up-Regulation; Adaptation, Physiological; Saccharomyces cerevisiae - proteiny; Osmotic Pressure; Ion Transport; Mitogen-Activated Protein Kinases; Saccharomyces cerevisiae Proteins; mitogenem aktivované proteinkinasy; osmotický tlak; Saccharomyces cerevisiae; fyziologická adaptace; membránové proteiny; iontový transport; Sodium-Hydrogen Exchangers; terciární struktura proteinů; Protein Structure, Tertiary; regulace genové exprese u hub; Gene Expression Regulation, Fungal; Na(+)-H(+) antiport